PREDICTIVE FACTORS FOR PROPHYLAXIS EFFECT OF NAPROXEN IN POST ENDOSCOPIC PANCREATITIS - Tanaj, Halil Nebih; Kondov, Goran; Krasniqi, Shaip (Journal of Morphological Sciences; Vol 5 No 2 (2022): JMS, 2022)
Endoscopic retrograde cholangiopancreatography (ERCP) can be associated with complications like post-ERCP pancreatitis (PEP). We aimed to examine the possible influence of selective demographic and clinical factors on efficacy of periprocedural 500 mg Naproxen single dose rectal administration in prevention of PEP in patients after diagnostic or therapeutic ERCP. This randomized prospective mono-centric clinical study was implemented during January-April 2022 on 30 patients referred for ERCP at the University Clinical Center of Kosovo-Prishtina. Before ERCP, all patients received periprocedural 500mg Naproxen single dose rectal administration in prevention of PEP. The levels of amylase, lipase, and CRP were measured before ERCP, and 4/24h after. The incidence of PEP was 16,67% (5/ 30) – 2 (11,76%) of the male and 3 (23,08%) of the female (p=0,4101). No significant differences between the patients without/with PEP was found related to age (p=0,8674), BMI (p=0,5591) and duration of procedure (p=0,5590). Pancreatic duct wire cannulation happened in 5 (16,67%) patients, while only 2 (40%) of them developed PEP. Amylases levels 24h after ERCP were significantly higher in patients with PEP (p=0,0005). Between patients without/with PEP there were significant differences in lipase levels before/4h/24h after ERCP for p=0,0451 vs. p=0,0278 vs. p=0,005 respectively. Related to CRP levels, no significant difference was found between the groups at any measurement time. Analyzed potential influencing factors didn’t show significant influence on efficacy of Naproxen in prevention of PEP after ERCP. More extensive controlled trials are underway in Republic of Kosovo to precise the effects of Naproxen in reduction of PEP after ERCP. Key words: Naproxen; nonsteroidal anti-inflammatorydrugs; pancreatic duct cannulation; post-endoscopicretrograde cholangiopancreatography; pancreatitis;